Ultrasound characteristics of abdominal vascular compression syndromes - Liu, Yan; Zheng, Haining; Wang, Xiaoqing; Wang, Zi; Zhu, Qiang; Wen, Chaoyang; Tong, Yisha (Frontiers in Cardiovascular Medicine, 2023)
Abdominal vascular compression syndrome (AVCS) is caused by the compression of abdominal blood vessels by adjacent structures or the compression of abdominal organs by neighboring blood vessels. Such compressions can result in a variety of clinical symptoms. They are not commonly seen in ultrasound practices, and their presence may have been underrecognized and underdiagnosed. This article reviews the clinical features, ultrasound characteristics, and diagnostic criteria of four types of AVCS, namely, celiac artery compression syndrome, renal vein compression syndrome, iliac vein compression syndrome, and superior mesenteric artery syndrome to increase awareness of these conditions among ultrasound practitioners. The ultrasound criteria for AVCS are primarily based on studies with small sample sizes, and therefore, it is important to exercise caution if these criteria are used.